Robotic surgery in pediatric urology: Current status. Issue 4 (27th September 2018) - Mizuno, Kentaro; Kojima, Yoshiyuki; Nishio, Hidenori; Hoshi, Seiji; Sato, Yuichi; Hayashi, Yutaro
Abstract: Robot‐assisted laparoscopic surgery (RALS) has been increasingly embraced in the fields of adult and pediatric urology, especially in North America and Europe. The advantages of a stable magnified 3‐D view, tremor filtering, and motion scaling allow for precise intracorporeal exposure and suturing. Because most surgeries are performed as reconstructive rather than excision procedures, the robotic platform is particularly feasible for the field of pediatric urology. In this review, we summarize the recent viewpoints on RALS, such as pyeloplasty, ureteral reimplantation, bladder neck reconstruction, bladder neck sling, appendicovesicostomy, bladder diverticulectomy, and treatments for ureterocele or ectopic ureters, and we also critically summarize the current status of the literature. Based on our initial experience, RALS is technically feasible for pediatric patients and may be achieved with comparable surgical outcomes. RALS is also associated with reduced morbidity compared to open surgery to conventional laparoscopic surgery. This evolution will offer an alternative in the treatment pediatric patients, along with improved care and patient quality of life. Further large case series and randomized controlled trials that investigate the robotic platform's technological improvements will help to expand indications of RALS in the field of pediatric urology.